2011
DOI: 10.1109/titb.2011.2131670
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive Assessment of Motor Patterns During Sleep Based on Mattress Indentation Measurements

Abstract: This study investigates how integrated bed measurements can be used to assess motor patterns (movements and postures) during sleep. An algorithm has been developed that detects movements based on the time derivate of mattress surface indentation. After each movement, the algorithm recognizes the adopted sleep posture based on an image feature vector and an optimal separating hyperplane constructed with the theory of support vector machines. The developed algorithm has been tested on a dataset of 30 fully recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Although it has been shown that during the sleep the amount of motion disturbances is minimal, about 3% as reported in [22], we still want heartbeat detection cope with those as efficiently as possible. Convergence tests in Section IV-C point out that an entirely missed detection may cause misplacement of not more than four subsequent heartbeat detections.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that during the sleep the amount of motion disturbances is minimal, about 3% as reported in [22], we still want heartbeat detection cope with those as efficiently as possible. Convergence tests in Section IV-C point out that an entirely missed detection may cause misplacement of not more than four subsequent heartbeat detections.…”
Section: Discussionmentioning
confidence: 99%
“…Indentation was continuously measured and recorded throughout the nights at a sampling rate of 1 Hz. The main sleep postures (left/right lateral, prone, supine) were estimated from the indentation data using a Support Vector Machine (SVM) classifier, that used five features according to the classification scheme proposed by Verhaert et al [22]. This algorithm allows posture detection with an overall accuracy of 92%.…”
Section: Measurementsmentioning
confidence: 99%
“…The validated study found self-report to be accurate for the primary sleep postures of supine, sidelying and prone, but did not report any reliability data [25]. For postures described as intermediate postures, self-report has not been examined [27].…”
Section: Introductionmentioning
confidence: 99%